The economic burden of smoking in California. Issue 3 (25th August 2004) - Max, W; Rice, D P; Sung, H-Y; Zhang, X; Miller, L
Abstract : Objective: To develop estimates of the direct and indirect costs of smoking for California in 1999. Methods: A prevalence based approach was used to estimate the annual costs of smoking. Econometric models were used to estimate the smoking attributable fraction (SAF) for direct costs (hospitalisations, ambulatory care, prescription drugs, home health care, and nursing home services) and indirect costs due to lost productivity from smoking related illness. The models controlled for socioeconomic factors and other risk behaviours. Epidemiological methods were used to estimate the SAF for indirect costs due to lost productivity from premature deaths. The SAFs were applied to total health care expenditures, days lost, and deaths to obtain smoking attributable total costs. Results: In 1999, the total costs of smoking in California were $15.9 billion, $475 per resident, and $3331 per smoker. Direct costs were $8.6 billion (54% of the total), indirect costs due to lost productivity from illness were $1.5 billion (10%), and indirect costs due to premature deaths were $5.7 billion (36%). The cost of smoking was $9.4 billion for men and $6.3 billion for women. There were 43 137 deaths attributed to smoking, representing a total of 535 000 years of life lost. The value of life lost per death averaged $132 000, or 12.4 years. Conclusions: California smoking related costs are high. The cost methodology presented is useful for other states and nations interested in estimating their costs of smoking. Cost estimates can be used to evaluate the level of cigarette taxes and other policies related to smoking.